2021
DOI: 10.1182/blood-2021-152242
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Assessment of Prior Treatment Patterns in Patients Receiving Belantamab Mafodotin Using a Longitudinal Pharmacy and Medical Open Source Claims Database

Abstract: Introduction: Belantamab mafodotin (belamaf) is a first-in-class B-cell maturation antigen-targeting antibody-drug conjugate, with a manageable adverse event profile, that has shown durable efficacy in a broad range of patients with relapsed or refractory multiple myeloma (RRMM) (Lonial et al., Lancet Oncol. 2020). As belamaf is an approved therapy, it is important to understand how it is being integrated into the management of patients with RRMM. The aim of this analysis was to examine baseline demographic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…TTD was defined as time in months from the first treatment initiation to the discontinuation (i.e., gap >60 days between last supply and next prescription refill). For discontinuation, a gap of 60 days was considered appropriate based on the following: (1) review of prescription day supply across all CDK4/6 inhibitor refills, which showed that almost all patients (99%) received a supply of 28 days or fewer and (2) prior literature assessing discontinuation of oral cancer medications 17,18 . Because our intent was to compare persistence between the individual agents in the same class and because a patient is most likely to switch from one CDK4/6 inhibitor (e.g., palbociclib) to another (e.g., ribociclib) because of progression 19 or toxicity, 20 such a switch was considered a discontinuation event.…”
Section: Methodsmentioning
confidence: 99%
“…TTD was defined as time in months from the first treatment initiation to the discontinuation (i.e., gap >60 days between last supply and next prescription refill). For discontinuation, a gap of 60 days was considered appropriate based on the following: (1) review of prescription day supply across all CDK4/6 inhibitor refills, which showed that almost all patients (99%) received a supply of 28 days or fewer and (2) prior literature assessing discontinuation of oral cancer medications 17,18 . Because our intent was to compare persistence between the individual agents in the same class and because a patient is most likely to switch from one CDK4/6 inhibitor (e.g., palbociclib) to another (e.g., ribociclib) because of progression 19 or toxicity, 20 such a switch was considered a discontinuation event.…”
Section: Methodsmentioning
confidence: 99%